Anthostomelloides krabiensis gen. Et sp. Nov. (xylariaceae) from Pandanus odorifer (pandanaceae) - Saowaluck Tibpromma (2018)
© TÜBİTAK. An Anthostomella-like taxon was obtained from Pandanus odorifer (Forssk.) Kuntze (Pandanaceae) collected in Krabi Province in Thailand. Morphological data plus phylogenetic analyses of combined ITS, LSU, RPB2, and β-tubulin sequence data clearly separate this Anthostomella-like taxon from other known genera in Xylariaceae. In this paper, we introduce this taxon as a new genus, Anthostomelloides, in the family Xylariaceae, with A. Krabiensis as the type. A detailed morphological description, phylogenetic tree, photomicrographs of A. Krabiensis, keys to Anthostomella-like genera, and a comparison of A. Krabiensis with the morphologically similar taxa in Xylariaceae are provided.